Association between sedentary behavior and risk of cognitive decline or mild cognitive impairment among the elderly: a systematic review and meta-analysis - Cai, Xiao-ye; Qian, Guo-ping; Wang, Feng; Zhang, Ming-yang; Da, Ying-juan; Liang, Jing-hong (Frontiers in Neuroscience, 2023)
Background: Existing evidence on the association between sedentary behavior (SB) and cognitive function remains inconclusive. Therefore, this study investigated the association between SB and risk of cognitive decline (CD) or mild cognitive impairment (MCI) in the elderly. Methods: A comprehensive search was independently conducted by two researchers (XC and GQ) in seven electronic databases, including Medline (via PubMed), China Biology Medicine, Embase, Web of Science, China National Knowledge Infrastructure, Wanfang Database, and VIP database for Chinese technical periodicals, covering studies published from database inception to June 2023. Studies that investigated the relationship between SB and risk of CD or MCI in the elderly were included. The quality of the literature was assessed using the Newcastle-Ottawa Scale (NOS) and the Agency for Healthcare Research and Quality (AHRQ) assessment tools. The combined effect size analysis, subgroup analysis, and publication bias assessment were performed using STATA 14.0. Results: A total of 13 cross-sectional and 6 cohort studies involving 81,791 individuals were included, comprising 17 high-quality studies and 2 medium-quality studies. We found that SB was significantly associated with an increased risk of CD [odds ratio (OR) = 1.69, 95% confidence intervals (CI): 1.47-1.94] or MCI (OR = 1.34, 95% CI: 1.14-1.56) among the elderly. Subgroup analysis stratified according to comorbidity, lifestyle, family structure, publication year, and region showed statistical differences between groups, and the consistency of the results revealed the sources of the heterogeneity. Conclusion: This meta-analysis showed that SB is positively associated with risk of CD or MCI in the elderly, providing a higher level of evidence for the promotion of healthy behaviors by clinicians and health policy makers. Due to the number and quality of the included articles, more high-quality longitudinal studies are needed to further confirm our findings.